EDUKASI DAN LITERASI PRODUK BANK SYARIAH BAGI SANTRI PONDOK PESANTREN AL KAUTSAR PEKANBARU - Mohd Ario Wahdi Elsye; Wahyi Busyro; Rika Septianingsih; Muhammad Syahrullah Umar (Jurnal Pengabdian UntukMu NegeRI, 2018)
Muhammadiyah University of Riau is one of universities in Riau and every college must do catur dharma which is the vision of all universities in Indonesia. One of the forms of catur dharma college is to carry out community service. Community service is an activity of academic community that utilizes science and technology to advance people's prosperity and educate the life of the nation. The form of community service undertaken by Sharia Banking Lecturers is holding a seminar with the theme “Education and Literation Of Sharia Bank Product For Student of Pondok Pesantren Al-Kautsar Pekanbaru". After the holding of this seminar is expected students understand Islamic bank products and can utilize Islamic bank products well. Keywords: Education, Literacy, Product, Islamic Bank.